Peningkatan Kompetensi dan Etika Bekerja Melalui Pelatihan Bahasa Jepang di PT Toray International Matsuoka Winner - Prasetya, Dany Buyung Yudha; Oesman, Andy Moorad; Sunahrowi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Work ethics and foreign language skills are essential for the professional, especially in a multinational corporate environment, where people who work have different cultures, languages, and nationalities. That is confirmed by observations at PT Toray International Matsuoka Winner Industries Semarang (PT TIMW). With daily interactions with Japanese clients and college, an understanding of the work ethics of Japanese corporations and proficiency in Japanese is necessary. The participants first studied Japanese corporate work ethics to improve PT TIMW staff's professional skills. Furthermore, ethical knowledge is covered by studying Japanese, which correlates to the office and business activities carried out by PT TIMW. The Japanese class training was attended by related department staff with the highest intensity of interacting with Japanese colleges and clients. Pair conversation activities were carried out to support the simulation of work situations related to production quantities and activities that indicate time. The tricky part was when the participants communicated by using numbers because there were differences in how to count between Indonesian and Japanese. The training showed good results where the participants could answer the mini-tests in each session. Pictures in textbook show an excellent impact in helping participants to imagine concepts and assist conversational activities in Japanese.